Repassivation underneath salt film on stainless steel pits. (15th July 2022) - Li, Tianshu; Frankel, Gerald S.
Abstract: The repassivation temperature ( T rp ) of one-dimensional artificial pits made from 316L stainless steel was investigated in 3.5 wt.% NaCl by downward temperature scanning. For a given pit depth, T rp exhibited an unexpected "S" dependence on applied potential. Further analysis shows that this relationship is derived from repassivation underneath the salt film, which is different from repassivation that occurs when the concentration of metal cations at the pit surface decreases below a critical value. This indicates that there exists a reversal in the effect of the salt film on pit growth stability, which depends on temperature, applied potential, and pit depth. Highlights: Repassivation temperature ( T rp ) of SS316L 1D pit decreases with increasing pit depth. T rp measured at a fixed pit depth exhibits an "S" dependence on applied potential. The "S" dependence is derived from the repassivation underneath the salt film. p H at metal/salt film interface increases with increasing applied potential. There exists a reversal in the effect of salt film on pit growth stability.